Gwarancje swobody sumienia sędziego w procesie cywilnym: [The guarantees of freedom of the judge's conscience in civil law procedures] (Studia Prawnicze / The Legal Studies, 2008)
Proces wymierzania sprawiedliwości wymaga wielkiego wkładu myśli, wiedzy i humanizmu. W procesie tym sędzia ma przyznaną szeroką władzę dyskrecjonalną, która uprawnia do wyboru przepisu prawnego, swobody interpretacyjnej i dowodowej oraz wyboru konsekwencji prawnej. Sędzia, oceniając fakty i dowody, mimo woli łączy prawo ze swoim wewnętrznym poczuciem sprawiedliwości, jako że wszelka wizja rzeczywistości jest raczej jej subiektywnym odtworzeniem aniżeli bezpośrednim widzeniem. Opierając się na pewnych wskazówkach, biorąc pod uwagę określone fakty lub je odpowiednio interpretując, sędzia może stworzyć inny obraz rzeczywistości i wyprowadzić z niego inne zastosowanie norm prawnych. Atrybut władzy dyskrecjonalnej nie uprawnia jednak do dowolności i arbitralności. Granice dyskrecjonalności i swobody sędziego wyznacza konstytucyjna zasada podległości sędziego Konstytucji i ustawom. W ujęciu pozytywnym oznacza to, że sędzia orzeka, opierając się tylko na prawie oraz zgodnie ze swoim sumieniem i wewnętrznym przekonaniem, natomiast w ujęciu negatywnym, że nikt z zewnątrz nie może wywierać na niego jakiegokolwiek nacisku.  This article introduces the guarantees of freedom of the judge's conscience in civil law procedures. Judges settle disputes and administer justice. Judges resolve conflicts related to private interests or the public interest. The results of their deci sions are real and fundamental for human lives. Verdicts given by them decide the rights to freedom and property of the people; sometimes they also define the rights and duties of entities. Judges are subordinated to the constitution and laws. Judges vow to administer justice not only according to law. They take an oath to administer justice according to their conscience. The conscience defines behavioral directives based on the category of "good" and "evil". Conscience is a hypothetical ability or faculty that distinguishes whether our actions are right or wrong. The conscience has an ethical, axiologi cal and legal dimension There are seven guarantees of freedom of the judge's conscience in civil law procedures. First, judges are independent, they are subordinated only to the con stitution and laws. Judges are privileged to immunity and cannot be dismissed. The independence of the judiciary is the basic right and freedom. Second, Judges are obliged to implement the actions specified in the law, while following the principle of impartiality and equal treatment of all zens, but they have the right to interpret legal regulations. Third, judicial Discretion, vague terms, gener al clauses and decision margins allow for individual decisions. Fourth, evidence confirming facts in the case are evaluated in accordance with the principle of free evaluation of evidence. Free does not mean discretionary, the judge evalu ates their reliability and strength of evidence on the basis of regulations, with the principle of correct reasoning, recommendation of knowledge and life experi ence, Fifth, the resolution of a case is not based on the mechanical deduction of consequences based on guidelines, being the general norms, but on the identifica tion of an optimal solution. During the evidence hearing the judge considers and simultaneously determines which norms should be applied to the specific case and determines the legal grounds for the decision. Sixth, the judge has the right to votum separatum. Finally, judges are not obliged to apply judgment. They can depart from the interpretation defined in line of judgment if they consider that a change in the interpretation would better support justice, Judges have the free dom of thought and making decisions. The judge's decisions in every case can't be mechanical deductions. This is rather more like finding the best solution and conviction of the optimal, well-ar gued decision, justified by the applied legal regulations and the conscience. The conscience causes that the judge's verdicts are just and have human dimensions.